Synthesis and Cytotoxic Activity of Triterpenoid Thiazoles Derived from Allobetulin, Methyl Betulonate, Methyl Oleanonate, and Oleanonic Acid - Borkova, Lucie; Adamek, Richard; Kalina, Petr; Drašar, Pavel; Dzubak, Petr; Gurska, Sona; Rehulka, Jiri; Hajduch, Marian; Urban, Milan; Sarek, Jan (ChemMedChem, 2017)
A total of 41 new triterpenoids were prepared from allobetulone, methyl betulonate, methyl oleanonate, and oleanonic acid to study their influence on cancer cells. Each 3-oxotriterpene was brominated at C2 and substituted with thiocyanate; subsequent cyclization with the appropriate ammonium salts gave N-substituted thiazoles. All compounds were tested for their in vitro cytotoxic activity on eight cancer cell lines and two non-cancer fibroblasts. 2-Bromoallobetulone (2 b) methyl 2-bromobetulonate (3 b), 2-bromooleanonic acid (5 b), and 2-thiocyanooleanonic acid (5 c) were best, with IC50 values less than 10 μm against CCRF-CEM cells (e.g., 3 b: IC50 =2.9 μm) as well as 2'-(diethylamino)olean-12(13)-eno[2,3-d]thiazole-28-oic acid (5 f, IC50 =9.7 μm) and 2'-(N-methylpiperazino)olean-12(13)-eno[2,3-d]thiazole-28-oic acid (5 k, IC50 =11.4 μm). Compound 5 c leads to the accumulation of cells in the G2 phase of the cell cycle and inhibits RNA and DNA synthesis significantly at 1×IC50 . The G2 /M cell-cycle arrest probably corresponds to the inhibition of DNA/RNA synthesis, similar to the mechanism of action of actinomycin D. Compound 5 c is new, active, and nontoxic; it is therefore the most promising compound in this series for future drug development. Methyl 2-bromobetulonate (3 b) and methyl 2-thiocyanometulonate (3 c) were found to inhibit nucleic acid synthesis only at 5×IC50 . We assume that in 3 b and 3 c (unlike in 5 c), DNA/RNA inhibition is a nonspecific event, and an unknown primary cytotoxic target is activated at 1×IC50 or lower concentration.
Keywords: kontrolní body M fáze buněčného cyklu; apoptóza; kyselina olenalová; Cell Line, Tumor; Thiazoles; Apoptosis; screeningové testy protinádorových léčiv; M Phase Cell Cycle Checkpoints; thiazoly; Structure-Activity Relationship; lidé; Antineoplastic Agents; protinádorové látky; triterpeny; Oleanolic Acid; G2 Phase Cell Cycle Checkpoints; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; Triterpenes; kontrolní body fáze G2 buněčného cyklu; nádorové buněčné linie; Humans